UTILISASI PELAYANAN KESEHATAN: PROBLEM ANTARA PEMERATAAN DAN EFISIENSI (Studi di Wilayah Pedesaan Kabupaten Purworejo) - Ambar Widaningrum (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2003)
Undoubtly, an accessible and adequate basic health service is priority for poverty reduction and more equitable development. Underutilization of health services is still a major concern for policy makers and constitutes the prime barrier to the large scale success of health programs. Information on the determinants and patterns of health care use can identify problems in organization and delivery that may result in underutilization. Based on the research findings in rural Purworejo, delivering services for the rural and poor people are in conflict with the objective to generate revenue. Many potential beneficiaries never get to adequate health services, because of the multiple non-financial constraints either from the demand side or the supply side. In order to enhance equitable utilization of public health services, strong commitment to apply investment in accessibility is certainly needed.